Characterization of the global structure of low methoxyl pectin in solution. (April 2015) - Fishman, Marshall L.; Chau, Hoa K.; Qi, Phoebe X.; Hotchkiss, Arland T.; Garcia, Rafael A.; Cooke, Peter H.
Abstract: Low methoxyl citrus pectin (LMP) and amidated low methoxyl pectin (LMAP) were characterized by high performance size exclusion chromatography (HPSEC) with online light scattering (LS), intrinsic viscosity ( η w ), differential refractive index (dRI) and ultra-violet (UV) detection, by amino acid analysis (AAA) and by atomic force microscopy (AFM). HPSEC revealed the following: the weight average molar mass ( M w ), ranged 103–288 × 10 3  Da, ( η w ), ranged 2.69–4.27 dL/g, radius of gyration (Rgz ), was 28.6–49.5 nm and hydrated radius (Rhzv ), was 26.3–41.8 nm. The presence of phenylalanine and tyrosine residues as shown by the UV absorbance at 278 nm in the high molar mass range is indicative of protein or fragments associated with LMP derived from citrus fruit. The ρ value (Rgz /Rhzv ) as a function of molar mass indicated that high molar mass pectin was more compact in shape than intermediate molar mass pectin. AFM images in this study and earlier studies indicate that high methoxyl pectin (HMP) and LMP form network structures in aqueous solution. Unlike HMP networks, LMP networks do not dissociate when dissolved in water at concentrations that are less than 6.6 μg/mL. Furthermore, AFM images, M w and η w values for LMP and LMAP indicate that little or no added sugar is bound. Graphical abstract: Highlights: M w, η w, Rgz, Rhzv and amino acid content were determined for LMP. LMP forms stronger network structures in solution than HMP. Protein or its fragments interact or co-elute with both high and intermediate sized LMP. Extension of LMP and LMAP pass through a maximum with decreasing molar mass.